2019
DOI: 10.3390/pr7100697
|View full text |Cite
|
Sign up to set email alerts
|

PIV and Statistical Analysis of a Swirling Bed Process Carried out Using a Hybrid Model of Axial Blade Distributor

Abstract: : An air distributor is a major component of industrial fluidized beds and its design significantly affects the quality of fluidization. In this study, a hybrid design of an annular distributor was tested for swirling fluidized beds (SFBs). Using this distributor design, a bed was operated in its uniform swirling regime of operation. A high-speed imaging method was used to capture images of the fluidized bed of particles. These images were processed using a binary cross-correlation technique and analyzed throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The velocity at which the bed started to rise is the minimum fluidization velocity. Shukrullah et al [33] reported similar trend of the bed remaining constant prior to Umf and rising continuously when the air velocity was increased beyond Umf value.…”
Section: Effect Of Temperature On Bed Porositymentioning
confidence: 82%
“…The velocity at which the bed started to rise is the minimum fluidization velocity. Shukrullah et al [33] reported similar trend of the bed remaining constant prior to Umf and rising continuously when the air velocity was increased beyond Umf value.…”
Section: Effect Of Temperature On Bed Porositymentioning
confidence: 82%